Magnetocaloric-transport properties correlation in doped manganites. (May 2016) - Mohamed, Abd El-Moez A.; Hernando, B.; Ahmed, A.M.
Abstract: This investigation is interested in studying the relation between magnetocaloric effect and transport properties in La0.7 Ba0.3 MnO3 manganite compound. The resistivity shows a metal–semiconductor transition at Tms temperature near to its reported Curie temperature ( T c ). Magnetic field application decreases resistivity and increases Tms towards higher temperatures. The magnetoresistance shows a peak around Tc and increases in value with the applied magnetic field. A similar behavior has been observed between magnetic entropy change (Δ S ), resistivity and magnetoresistance around Tc, this is attributed to the spin order/disorder feature that plays a main role in the magnetocaloric-transport correlation. In spite of this similarity, the correspondence among the experimental Δ S and Δ S based resistivity calculations is missing because of lattice polarons effect on resistivity as a result of the electron–phonon interaction. The magnetocaloric–magnetoresistance relation is also studied and results show the contribution of additional factors in the magnetoresistance mechanism other than spin disorder suppression as Jahn–Teller effect and electronic phase separation. Highlights: The correlation between magnetocaloric effect and transport properties is studied. Spin order/disorder feature plays important role in this correlation. Δ S, ρ and MR shows the same behavior around Curie temperature. The difference between experimental Δ S and Δ S based ρ due to lattice polaron. The difference between Δ S and MR broadness reveals additional contribution in MR.